Much more than just an ingredient: Palm oil and its consumer perspectives in Indonesia - Sophie-Dorothe Lieke; Andriyono Kilat Adhi (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
While consumers in palm oil-importing countries mainly encounter palm oil as an ingredient, consumers in palm oil-producing nations additionally rely on it as their primary cooking oil. Using focus group discussions across low, middle- and high-income groups (10 groups, n=81), this paper considers underrepresented consumer perspectives by examining how the situational context in urban Indonesia influences the significance of palm oil and its consumption patterns. Palm oil catalyzes cultural practices, ensures food security and contributes to income generation. We identify perceived structural and cultural barriers inhibiting consumer-driven and local demand for more sustainable palm oil, and importantly who in consumers' eyes carry the responsibility and power to materialise these changes. This ensures that the call for improved food sustainability is not unilateral, but that action is tailored and administered at appropriate levels. Nonetheless, challenges persist as for Indonesians palm oil truly serves as so much more than just an ingredient.
Keywords: 330; consumer behaviour; Indonesia; palm oil; socio-economic status; sustainability